The Implementation of Muhadharah Activities for Student Talent Development at MTsN 11 Agam: Pelaksanaan Kegiatan Muhadharah Terhadap Pengembangan Bakat Siswa Di MTsN 11 Agam - Rezkia Ramadhan; M Isnando Tamrin; Arif Fiandi (Institute of Educational, Research, and Community Service, 2023)
Muhadharah is one of the self-development activities that is usually carried out at school and at TPA, where this activity indicates that students can display and deliver a series of event activities in front of their friends in order to develop their talents and potential. The aim of this research is to determine the role of muhadharah activities in developing student talents at MTsN 11 Agam. The research methodology used in this research is a qualitative approach. The data collection techniques used were observation, interviews and documentation. The results of this research are that muhadharah activities play a very important role in developing students' talents. In muhadharah activities, students are given the opportunity to display their various talents under the guidance of the teacher, such as master of ceremonies (MC), speech (public speaking), nasyid, hafiz Quran, the art of reading the Quran, and other activities according to the students' talents. It is hoped that MTsN 11 Agam will further maximize the implementation of muhadharah, so that it can maximize student talent development.